Exploring patient satisfaction with community pharmacy services in the United Arab Emirates: Implications for quality improvement - Zelal Kharaba; Karem H. Alzoubi; Sayer Al-Azzam; Ahmad Al-Azayzih; Ahmad Y. Abuhelwa; Feras Jirjees; Anan Jarab; Azza Ramadan; Shoroq M. Altawalbeh; Dania Rahhal; Munazza Ahmed; Laila A. Ibrahim; et al. (PLoS ONE, 2026)
Introduction Patient satisfaction is a critical metric for enhancing service quality, meeting regulatory standards, and validating patient-reported outcomes in healthcare. Community pharmacies play a vital role in healthcare delivery, yet there is limited research on patient satisfaction with these services in the UAE. Aims This study aims to identify key factors influencing patient satisfaction with pharmaceutical care services provided by community pharmacies in the UAE. Methods A cross-sectional, questionnaire-based study was conducted from December 1st, 2023, to April 30th, 2024. A systematic intercept sampling method was used to ensure a representative sample of 505 patients from various regions of the UAE. Data were collected through structured questionnaires covering demographic details, pharmacy visit experiences, and satisfaction levels. Statistical analyses, including chi-square tests, t-tests, and binary logistic regression, were performed using SPSS 27. Results The study found that most participants most frequently used chain pharmacies (62.38%) and were highly satisfied with factors like lighting (91.29%) and pharmacist attentiveness (83.96%). Key drivers of satisfaction included convenient locations, accessible designs, and communication-related factors.. However, challenges such as the lack of private counseling areas (59.01%), limited access to medical files (77.62%), and inadequate prescription areas for private conversations (53.29%) were highlighted. Satisfaction was significantly lower in the Northern Emirates compared to Abu Dhabi, while differences involving Al Ain did not reach statistical significance. Providing sufficient time for medication advice (OR: 16.21, p < 0.001) and ease of waiting times (OR: 4.29, p = 0.016) improved satisfaction. Conclusion The findings underscore the importance of both environmental and interpersonal factors in shaping patient satisfaction with community pharmacies. Enhancing pharmacy accessibility, communication, and the quality of pharmacist-patient interactions can significantly improve patient experiences. Future research should further explore overall satisfaction and investigate targeted improvements in pharmacy practices across different regions and settings.